Monitoring and impact of fluconazole serum and cerebrospinal fluid concentration in HIV-associated cryptococcal meningitis-infected patients - W. Manosuthi (2018)
Objectives:The aim of the present study was to assess fluconazole pharmacokinetic measures in serum and cerebrospinal fluid (CSF); and the correlation of these measures with clinical outcomes of invasive fungal infections. Methods:A randomized trial was conducted in HIV-infected patients receiving three different regimens of fluconazole plus amphotericin B (AmB) for the treatment of cryptococcal meningitis. Regimens included fluconazole 400 mg/day+AmB (AmB+Fluc400) or fluconazole 800 mg/day+AmB (AmB+Fluc800) (14 days followed by fluconazole alone at the randomized dose for 56 days); or AmB alone for 14 days followed by fluconazole 400 mg/day for 56 days. Serum (at 24 h after dosing) and CSF samples were taken at baseline and days 14 and 70 (serum only) for fluconazole measurement, using gas-liquid chromatography. Results: Sixty-four treated patients had fluconazole measurements: 11 in the AmB group, 12 in the AmB+Fluc400 group and 41 in the AmB+Fluc800 group. Day 14 serum concentration geometric means were 24.7 mg/L for AmB+Fluc400 and 37.0 mg/L for AmB+Fluc800. Correspondingly, CSF concentration geometric means were 25.1 mg/L and 32.7 mg/L. Day 14 Serum and CSF concentrations were highly correlated with AmB+Fluc800 (P<0.001, r=0.873) and AmB+Fluc400 (P=0.005, r=0.943). Increased serum area under the curve (AUC) appears to be associated with decreased mortality at day 70 (P=0.061, odds ratio=2.19) as well as with increased study composite endpoint success at days 42 and 70 (P=0.081, odds ratio=2.25 and 0.058, 2.89, respectively). Conclusion:High fluconazole dosage (800 mg/day) for the treatment of HIV-associated cryptococcal meningitis was associated with high serum and CSF fluconazole concentration. Overall, high serum and CSF concentration appear to be associated with increased survival and primary composite endpoint success. © 2009 British HIV Association.